Aplikasi Absensi Mahasiswa Meningkatkan Efisiensi dan Mencegah Kecurangan dalam Pencatatan Kehadiran - Abdul Rifai Wadjidi; Rifal Rifal; Sulfahmi Sulfahmi; Kurnia Prima Putra (Journal of Deep Learning, Computer Vision, and Digital Image Processing, 2023)
Attendance is the process of recording and monitoring the presence of individuals in an event, meeting, or specific activity. In an educational setting, attendance is used to monitor the presence of students in class. Attendance becomes part of the assessment given by instructors to students, which can affect the final grades received by the students. However, cheating often occurs among students regarding attendance in order to meet the minimum attendance requirement in teaching and learning activities. This practice of proxy attendance can harm the instructors, other students, and even the students who engage in such cheating. Additionally, the attendance sheets used to record attendance often suffer from damage. Yet, these attendance sheets will be used as reports related to teaching and learning activities within a semester. If these documents are damaged, it will affect the document verification process by the university. Therefore, we have designed the Student Attendance Application to facilitate and enhance the efficiency of recording student attendance in the campus environment.